THE INFLUENCE OF NURSE RESPONSIVENESS IN THERAPEUTIC COMMUNICATION PRACTICES ON PATIENT SATISFACTION IN INSTALATION INSTALATIONS RSNU TUBAN - Miftahul Munir; Muhammad Sudrajad (International Nutrition and Health Administrations Journal, 2022)
Background: Patient satisfaction is one of the indicators measured in the Hospital Minimum Service Standards. In the Inpatient Installation (IRNA) of the Tuban Hospital there are 17 indicators but only 9 are met (52.94%). One of them is patient satisfaction with an achievement of 74.35% of the standard set by the hospital of 82%. One of the causes of not achieving patient satisfaction is the high number of patient complaints regarding aspects of the competence of nurses in providing services, a total of 61 complaints during 2014-2021. Methods: The research questionnaire instrument used a Likert scale of 1-5 on the independent and dependent variables. The rating scale on the independent variable or nurse's responsiveness ranged from strongly disagree to strongly agree. Meanwhile, the rating scale for the dependent variable ranges from very dissatisfied to very satisfied. Results: Based on the results of the study, it can be concluded that there is a significant effect of responsiveness or responsiveness of 0.003 (<a=0.05). to patient satisfaction. This shows that the better the patient's assessment of the responsiveness of the nurse, the more patient satisfaction will increase at the Inpatient Installation (IRNA) of the Tuban Hospital. Conclusion: More than 20% of respondents' assessments are in the category of being satisfied with the nurse's response. The hospital needs to hold training on human resources, especially training in therapeutic communication between nurses and patients to maintain the quality of service at the hospital.